Study the effect of myopia on macular retinal thickness in adults by optical coherence tomography - kordoghli, Najwa; yousef, Habib; daher, Yara (Latakia University Journal -Medical Sciences Series, 2020)
Purpose : To study the relationship between macular thickness and degree of myopia in adults using Spectralis (SD-OCT) and the relationship with the axial length . Methods : 124 Syrian subject (178 eyes) participated in this study comprising 70 nonmyopic eyes and 108 myopic eyes ; 60 eyes with low myopia ، 28 eyes with moderate myopia، 20 eyes with high myopia. Visual acuity ، refractive errors after cycloplegia ، examination of the anterior segment using slit lamp ،indirect ophthalmoscopy and biomicroscopy ، intraocular pressure measurements ، axial length، and macular thickness using Spectralis (SD-OCT) were compared among 4 diagnostic groups. Results : : The average foveal thickness ( 1mm ring on the OCT retinal thickness map ) were significantly greater in myopic eyes and increases with the degree of myopia، the inner ring (1-3 mm) and the outer ring (3-6mm) thickness significantly lower in the high myopic eyes، there was a positive correlation between the axial length and the average foveal thickness ، negative correlation were found between axial length and average inner and outer ring macular thickness . Conclusion : macular thickness in myopic eyes is thicker at the center (fovea) ، inner/ outer ring macular thickness thinner in high myopia ، there is significant relationship between macular thickness and spherical equivalent/ axial length , and should be considered when these parameters are evaluated in eyes with retinal diseases . الهدف : دراسة علاقة ثخانة اللطخة الصفراء مع درجة الحسر لدى البالغين باستخدام التصوير البصري المقطعي المتماسك بالمجال الطيفي SD-OCT وعلاقة الثخانة مع الطول المحوري للعين . الطرائق : شارك بالدراسة 124مريضاً (178عين) توزعت العينة الى70 عين شاهد و108 عين حسيرة والمصنفين بحسب درجات قيمة المكافئ الكروي الى مجموعات ثلاثة : حسر خفيف(60 عين) ، حسر متوسط (28 عين) ، حسر شديد (20 عين) ، حيث تم فحص القدرة البصرية ، اسواء الانكسار بعد شل المطابقة ، فحص شامل للأقسام الامامية بالمصباح الشقي ، تنظير قعر العين ، فحص ضغط العين ، طول العين المحوري ، ثخانة اللطخة الصفراء بواسطة جهاز Spectralis SD-OCT وتم مقارنة النتائج بين المجموعات الأربعة . النتائج : ثخانة اللطخة الصفراء المركزية (1mm ) لدى الحسيرين كانت أعلى مقارنة بالشواهد بوجود فروقات ذات دلالة احصائية p-value = 0.001 وانها كانت في ازدياد مع زيادة درجة الحسر، ثخانة الحلقة الداخلية (1-3mm) والحلقة الخارجية(3-6mm ) كانت منخفضة بشكل واضح لدى مجموعة الحسر الشديد مقارنة بباقي المجموعات ، علاقة ارتباط ايجابية بين ثخانة المركز والطول المحوري للعين ، أما ثخانة الحلقة الداخلية والخارجية فارتبطت بعلاقة سلبية مع الطول المحوري للعين . الخلاصة : تكون اللطخة الصفراء لدى مرضى الحسر أثخن في المركز (النقرة) ، الحلقة الداخلية والخارجية لدى الحسر العالي ارق ، ثخانة اللطخة الصفراء مرتبطة مع قيمة المكافئ الكروي والطول المحوري للعين بعلاقة هامة احصائيا لذلك يجب أخذ هذه القيم بعين الاعتبار اثناء تقييم الامراض الشبكية في العيون الحسيرة .